Fruit Maturity Identification System - et. al., Sangeeta Kumari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In India most of population is dependent on agriculture, so we can integrate Internet of Things (IoT) and Image processing Technology with our agriculture to increase the growth of agriculture which in turn strengthens economy of our country. This paper aims to combine IoT and Image processing Technology for developing smart agriculture based System. The Farmers must take actions like Irrigation control and remote monitoring of farm to save natural water resources and to improve the growth of plant. Classification of fruits based on their maturity can be done by taking into consideration these two important features: color and size. Traditional methods of irrigation and manually evaluating the maturity of fruit by visual detection are prone to human error. The goal of system is to collect real time data of agriculture domains using cameras and sensors and send the data via Android app to farmers. The use of Internet technology to send collected information to farmers and controlling field remotely via Android app is the purpose of proposed system. The aim of smart farming system is to makes automatic irrigation possible. This reduces the manpower involved.